2012
DOI: 10.1016/j.ultrasmedbio.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficacy of Subharmonic Aided Pressure Estimation for Portal Vein Pressures and Portal Hypertension Monitoring

Abstract: The efficacy of using subharmonic emissions from Sonazoid microbubbles (GE Healthcare, Oslo, Norway) to track portal vein pressures and pressure changes was investigated in 14 canines using either slow- or high-flow models of portal hypertension (PH). A modified Logiq 9 scanner (GE Healthcare, Milwaukee, WI) operating in subharmonic mode (ftransmit:2.5MHz, freceive:1.25MHz) was used to collect RF data at 10-40% incident acoustic power levels with 2-4 transmit cycles (in triplicate), before and after inducing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 55 publications
(115 reference statements)
5
42
1
Order By: Relevance
“…Since its implementation on two modified commercial US scanners, SHAPE has been used to track dynamic pressures in vitro (12), to monitor interstitial fluid pressures in a swine melanoma model (13), and to separately measure left ventricular pressures and changes in portal pressures in canine models (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…Since its implementation on two modified commercial US scanners, SHAPE has been used to track dynamic pressures in vitro (12), to monitor interstitial fluid pressures in a swine melanoma model (13), and to separately measure left ventricular pressures and changes in portal pressures in canine models (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…A secondary goal of this study was to compare SHAPE’s performance with 4, 8 and 16 transmit cycles. The clinical relevance and in vivo applications of SHAPE have been documented [1-4]. The current study builds on previous in vitro and in vivo SHAPE studies [1-7] and solves the problem of determining optimum IAO levels to insonate the ultrasound contrast agents (UCAs) for SHAPE applications.…”
Section: Introductionmentioning
confidence: 99%
“…The current study builds on previous in vitro and in vivo SHAPE studies [1-7] and solves the problem of determining optimum IAO levels to insonate the ultrasound contrast agents (UCAs) for SHAPE applications. If successful, this approach may help eliminate the problems of acquiring and analyzing the data offline at all IAO levels as was done previously [1-3, 6] and, thus, pave the way for real-time clinical pressure monitoring applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study in canines reported the possibility of a subharmonic aided pressure estimation (SHAPE) in the estimation of portal pressure 33. The same group examined the clinical effect of the technique in human subjects and found a good overall agreement (r=0.82) between the SHAPE gradient (the portal and hepatic veins) and HVPG 34.…”
Section: Contrast-enhanced Usmentioning
confidence: 99%